Concepts and methods: Ethnopharmacological Database for Medicinal plants used in the Northern Morocco - Redouan, Fatima Zahrae; Yebouk, Cheikh; Merzouki , Ghizlan; Ouhtit, Rachid; Crisafulli, Alessandro; Picone, Rosa Maria; Gaetano Maurizio, Gargiulo; Merzouki, Abderrahmane (Ethnobotany Research and Applications, 2025)
Background: Northern Morocco is rich in biodiversity, notably medicinal plants. which considered the primary source of medicines and drug discovery due to their secondary metabolites and bioactive compounds that are pharmacologically applicable against several diseases. This study aims to design and develop a database to document the therapeutic uses practiced by the population of the PNTLS (catalog of medicinal plants), analyze the information obtained by species and by uses, comparing with recent literature (Andalusia and Sicily), and the historical data from ancient manuscripts, for to compare the conservation of plant knowledge in the space area and over time. Methods: The survey was carried out between 2014 and 2017 using semi-structured questionnaires in PNTLs. Data were gathered manually from scientific resources such as published scientific articles, books Ibn Al Baytar (13th century), De Materia Medica of Matthioli and Dioscorides of Laguna (16th century). The data were then organized and digitized into a database using: MySQL, PHP, WAMP, JAVA Script, and JavaScript. Results: The results obtained from the PNTLS (152 medicinal plants with 567 uses) were compared with the same species cited in current works from Andalusia (103 medicinal uses) and Sicily (94 medicinal uses), and with ancient works including Ibn Al Baytar (94 medicinal uses), Matthioli and Laguna (94 medicinal uses). Conclusion: The fieldwork data, traditional uses cited in the ancient work and an intuitive platform design, it a resource for preserving traditional plant knowledge, supporting scientific research and promoting sustainable use of medicinal plants in the region. Keywords: Ethnobotanical approach; Database; Medicinal plants; Talassemtane National Park (PNTLS).